Efeito da associação da fotobiomodulação e exercício físico em mulheres com osteoartrite de joelho sobre o nível de dor: ensaio clínico placebo-controlado randomizado duplo-cego - Pelloi, Suzana Cristina Pereira (2020)
OA is a degenerative disease with joint signs and symptoms associated with changes in the integrity of the articular cartilage, remodeling of the subchondral bones and local and adjacent tissue inflammation, clinically associated by joint pain and functional limitation. Pain is the biggest disabling factor, so it is important to investigate ways to improve it, and photobiomodulation (PBM) has been highlighted for promoting modulation of the inflammatory process and relief of pain of OA. The objective of this study was to verify whether the gradual increase in the dosage of FBM applied to the knee joint has more positive effects in the treatment of OA when combined with physical exercise, especially in relation to pain. Twenty-eight women, between 55 and 75 years old, with knee OA grades II and III, were allocated to the Physical Exercise Group associated with active PBM (PEAP), who received treatment with an eight-week exercise protocol associated with active irradiation of PBM and Physical Exercise Group associated with Placebo PBM (PEPP), which received the same treatment, but with placebo irradiation. PBM was performed with an 808nm laser, applied to the medial and lateral regions of the knee. The instruments used were (for assessment and reassessment) the Knee Injury and Osteoarthritis Outcome Score (KOOS) questionnaire, Visual Analogue Scale (VAS), digital algometer, Timed Up-and-Go Test (TUGT) and 6-minute walk test (6-MWT). The results obtained showed that there was an improvement in pain, symptoms and functionality in both groups, with no significant difference between them. It can be concluded that the exercise program was able to reduce the level of pain and increase the functional capacity of women affected by knee OA. However, the PBM used in the treatment regimen, with a progressive increase in the dose, did not optimize the positive results of the exercise program.